On some helminth parasites of the taruca, Hippocamelus antisensis (Mammalia: Artiodactyla) - Gomez-Puerta, Luis A. (2016)
This study presents three species of helminth parasites collected from a taruca (Hippocamelus antisensis) in Peru. Three helminth parasites from the taruca (Hippocamelus antisensis) are described in this report. An adult male taruca was remitted to the Veterinary Institute of Tropical and Highland Research (IVITA), Sede Maranganí, for the National Forest and Wildlife Service of Peru (SERFOR) for their respective necropsy. Two nematodes were collected from the digestive system, and 1 cyst was collected from the omentum. Morphometric characteristics of the specimens were evaluated for the parasitological diagnosis. Nematodes were diagnosed as Trichostrongylus axei and Mazamastrongylus sp.; on the other hand, the cyst was diagnosed as a metacestode of Taenia hydatigena. T. axei finding represents the first record for the taruca. A brief morphological description of each helminth and discussion about their hosts and distribution is done.